Efficacy of Distraction Methods on Procedural Pain and Anxiety by Applying Distraction Cards and Kaleidoscope in Children - Nejla Canbulat, PhD; Sevil İnal, PhD; Hacer Sönmezer, MSc (Elsevier, 2014)
Purpose: This study aims to investigate two different distraction methods, distraction cards and kaleidoscope, on pain and anxiety relief of children during phlebotomy. Methods: This study is a prospective, randomized and controlled trial. The sample consisted of 7-11 year-old children who required blood tests. Children were randomized into three groups: the distraction cards group, the kaleidoscope group, and the control group. Data were obtained by interviewing the children with their parents and the observer before and after the procedure. The pain levels of the children were assessed by the parent and observer reports as well as self report using the Wong Baker FACES Pain Rating Scale. The anxiety levels of children were assessed by parent and observer reports using Children Fear Scale. Results: One hundred and eighty-eight children (mean age, 8.8 ± 1.5 years) were included. The pain levels of children showed significant differences among the groups (p = .005). Both the distraction card group (2.41 ± 2.49) and the kaleidoscope group (3.10 ± 2.16) had lower pain levels than the control group did (4.44 ± 3.64). The distraction card group had the lowest pain levels (2.41 ± 2.49) among all groups. The procedural anxiety levels of children were significantly different among the groups (p = <.001). Both the distraction card group (1.10 ± 1.20) and the kaleidoscope group (1.61 ± 1.12) had lower anxiety levels than the control group did (2.41 ± 1.30). The distraction card group had the lowest anxiety levels (p = <.001). Conclusion: The distraction cards were the most effective method for pain and anxiety relief of children during phlebotomy. Also the distraction method with kaleidoscope was an effective method for pain and anxiety relief during phlebotomy in children.